Virtual sports teacher - A serious game in higher education - Kliem, A.; Wendel, V.; Winter, C.; Wiemeyer, J.; Göbel, S. (International Journal of Computer Science in Sport, 2012)
Virtual Sports Teacher is a Serious Game which is being developed by sports scientists, computer scientists and media scientists, funded by the HMWK (hessian Ministry of science and art). The primary target group of the game are physical education teacher students. In the game they can practice the procedure of a typical sport lesson, learn how to treat pupils and arrange different sport exercises. A Game Master, the course teacher of a university tutorial, can adapt the game at runtime according to the player`s performance. The Game Master is able to view important statistics, to modify difficulty or to trigger game events. In Section 1, we explain the need for new forms of teaching like Serious Games. In Section 2, we present the game Virtual Sports Teacher, followed by a detailed description of the didactical and Game Mastering concept in Section 3. In Section 4 we conclude with an overview of future work.